HUBUNGAN MOTIVASI DAN SIKAP DENGAN HASIL BELAJAR PADA MATA KULIAH KOMPUTER GRAFIS - Meldi Kurnia Yusri Ade Kurnia Yusri (Pedagogi: Jurnal Ilmu Pendidikan, 2016)
This research was motivated by the low student learning outcome at Curriculum and Technology of Education in Education of Sciences Faculty, State University of Padang. The purpose of this research was to reveal the relationship of learning motivation and learning attitudes with learning outcome of student TM 2013 semester 2 in KTP FIP UNP majors. This research used quantitative methods to the type of correlational research. The sample in this research were 77 students TM 2013 semester 2 in KTP FIP UNP majors, used Slovin formula with proportional random sampling technique. The research instrument was structured in the form of a questionnaire with Likert scale models, after being tested looking for validity and reliability. The data were analyzed using simple linear regression and multiple regression. The results showed that (1) There was a significant positive relationship between learning motivation and learning outcome of students TM 2013 semester 2 majoring in Curriculum and Educational of Technology at 0.492, (2) There was a significant positive relationship between the attitude of learning with learning outcome of students TM 2013 semesters 2 in Curriculum and Educational Technology majors by 0,646, (3) There was a significant positive relationship between learning motivation and learning attitude toward learning outcome for student TM 2013 semester 2 in Curriculum and Educational Technology majors at 0.702. Based on the findings of this study concluded that the two independent variables, namely learning motivation and learning attitude played a very important in improving learning outcome, in addition to other variables.